Experimental infections of different carp strains with the carp edema virus (CEV) give insights into the infection biology of the virus and indicate possible solutions to problems caused by koi sleepy disease (KSD) in carp aquaculture - Adamek, Mikolaj; Oschilewski, Anna; Wohlsein, Peter; Jung-Schroers, Verena; Teitge, Felix; Dawson, Andy; Gela, David; Piackova, Veronika; Kocour, Martin; Adamek, Jerzy; Bergmann, Sven M; Steinhagen, Dieter (Veterinary research, 2017)
Outbreaks of koi sleepy disease (KSD) caused by carp edema virus (CEV) may seriously affect populations of farmed common carp, one of the most important fish species for global food production. The present study shows further evidence for the involvement of CEV in outbreaks of KSD among carp and koi populations: in a series of infection experiments, CEV from two different genogroups could be transmitted to several strains of naïve common carp via cohabitation with fish infected with CEV. In recipient fish, clinical signs of KSD were induced. The virus load and viral gene expression results confirm gills as the target organ for CEV replication. Gill explants also allowed for a limited virus replication in vitro. The in vivo infection experiments revealed differences in the virulence of the two CEV genogroups which were associated with infections in koi or in common carp, with higher virulence towards the same fish variety as the donor fish. When the susceptibility of different carp strains to a CEV infection and the development of KSD were experimentally investigated, Amur wild carp showed to be relatively more resistant to the infection and did not develop clinical signs for KSD. However, the resistance could not be related to a higher magnitude of type I IFN responses of affected tissues. Despite not having a mechanistic explanation for the resistance of Amur wild carp to KSD, we recommend using this carp strain in breeding programs to limit potential losses caused by CEV in aquaculture.
Keywords: Gills; žábry; Aquaculture; mužské pohlaví; kapři; infekce vyvolané poxviry; Carps; ženské pohlaví; zvířata; nemoci ryb; Skin; Poxviridae; Fish Diseases; Female; vodní hospodářství; kůže; Male; Poxviridae Infections; Animals